P133 Using a cross sectional survey to establish a national picture of the activity, governance and delivery of condom distribution schemes in england, in the financial year 2015/16. (8th June 2017) - Ratna, Natasha; Nardone, Anthony; Hadley, Alison; Brigstock-Barron, Owen
Abstract : Introduction: Condoms remain a key intervention to prevent sexually transmitted infections (STI), pregnancy and HIV. C-Card is a type of condom distribution scheme (CDS) with condom demonstration and risk assessment at registration, after which free condoms are available to young people, in accessible locations. Aim: Review delivery and C-Card activity in England and its regions in financial year 2015/16, to inform policy, best practice, future monitoring and evaluation. Methods: An online survey was disseminated to sexual health commissioners of 152 upper tier local authorities (UTLA) in England between 17/12/2016 and 10/02/2017. Questionnaire domains collated information on service delivery structure, governance, user information, spend, product availability and provision, and other CDS. Results: 64% (98/152) of UTLAs completed the survey. 20 had both C-Card schemes and CDS, 57 had C-Card schemes, 14 had CDS and 7 had neither. 60 reported 4, 560 C-Card outlets. The three most common settings for C-Card schemes were pharmacies (1, 363, 30%), youth organisation and educational settings (1, 105, 24%) and general practice (996, 22%). In 2015/16, 77 UTLAs reported 65, 762 new C-Card user registrations, of which 70% were repeat users. Of 70 reporting product availability, 60 (86%) distributed condoms and lubricants. 28 distributed 896, 221 products, of which 85.8% were condoms, 13.7% were lubricants and 0.5% other. Estimated spend on condom schemes were £1, 491, 937. Discussion: Availability of CDS in most UTLAs and high repeated use of C-Card schemes suggest acceptability and popularity. Improved evaluation of C-Card schemes for STI, pregnancy and HIV prevention is needed to demonstrate their value.